2020
DOI: 10.7150/jca.36886
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of Hapto and Gremlin1 expression in extrahepatic cholangiocarcinoma

Abstract: Background: Some studies have demonstrated that Hapto and Gremlin1 play an important biological role in many neoplasms. However, the role of Hapto and Gremlin1 in extrahepatic cholangiocarcinoma (ECC) remains to be revealed. Thus, this study investigated the prognostic and clinicopathological significance of Hapto and Gremlin1 expression in ECC. Methods: We examined Hapto and Gremlin1 expression in 100 ECC, 30 peritumoral tissues, 10 adenoma and 15 normal biliary tract tissues using EnVision immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Then, the PSM analysis was incorporated to omit the bias selection between with mucinous and adeno CCA patients. Meanwhile the Kaplan-Meier survival analysis allowed us to determine the percentage of patients who survive a specific event ( 23 ). Before and after the PSM analysis, the patients were assessed for Kaplan-Meier survival analysis and showed no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the PSM analysis was incorporated to omit the bias selection between with mucinous and adeno CCA patients. Meanwhile the Kaplan-Meier survival analysis allowed us to determine the percentage of patients who survive a specific event ( 23 ). Before and after the PSM analysis, the patients were assessed for Kaplan-Meier survival analysis and showed no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GREM1 on the prognosis of malignant tumors remains elusive. Some studies have linked high GREM1 expression to poor prognosis in several malignancies, including ER-negative breast cancer [ 16 ], cervical cancer [ 61 ], ex-trahepatic cholangiocarcinoma [ 62 ], basal cell carcinoma [ 63 ] and renal cell carcinoma [ 64 ]. In CRC, high GREM1 protein expression has been associated with low tumor stage and extended survival [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the functionally relevant proteins, haptoglobin, was further selected for clinical verification using individual plasma samples. Haptoglobin is an acute phase protein which is mainly synthesized in liver and is reported to be overexpressed in various types of cancers including GBC and reported to promote cell proliferation, migration and invasion, which implies its role in pathophysiological process of GBC ( 31 33 ). Clinical verification of HP by quantitative ELISA in the present study showed significantly increased levels in GBC in comparison to controls (health volunteers and GSD cases) ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%